Subcellular protein overexpression to develop abiotic stress tolerant plants - Nouri, Mohammad-Zaman; Komatsu, Setsuko (Frontiers in Plant Science, 2013)
Environmental stresses are major factors limiting growth and development of crops. Plants respond to the stresses through a wide range of reactions from morphological changes to alterations in the patterns of protein expression. Understanding the mechanisms involved in the stress response is the first step to develop abiotic stress tolerant crops. Proteomics is a powerful tool in evaluating regulated proteins in the cell under stress and it is an efficient technique in studying stress tolerant plants. Because of the nature of abiotic stress, intracellular compartments play a main role in the stress response. Subcellular proteins such as ion and water transporters, ROS scavengers and the proteins related to signaling and transcriptional regulation are frequently reported as being involved in stress tolerance. Overexpression of stress-responsive protein through generation of transgenic plants is one the main practical approaches in production of tolerant plants. In this article, recent studies on transgenic plants overexpressing subcellular proteins are reviewed and the role of organelles and over-expressed proteins is classified.